An Integrated Approach to the Treatment of Severe Psoriasis: A Clinical Case - Lyudmila Smirnova (Journal of Global Pharma Technology, 2020)
Psoriasis is a disease of autoimmune origin, affecting not only the skin, but also the internal organs of a person. Currently, many methods of treating psoriasis are in use, which vary in effectiveness. The aim of this work is to analyze the results of complex physiotherapeutic and pharmacological treatment of a patient with severe psoriasis in comparison with the initial failed treatment with traditional pharmacological methods. The therapy was carried out in 2018-2019 (observation by a rheumatologist at the place of residence), after treatment that was unsuccessfully carried out in 2016 at the Institute of Rheumatology (Federal State Budget Scientific Institution "Scientific Research Institute of Rheumatology named after VA Nasonova") with an incorrect diagnosis of rheumatoid arthritis. In the secondary complex therapy, the following treatment methods were used: a) antihistamines (Chloropyramine 1.0 IM in the evening for 22 days, Chloropyramine 1 tablet 2 times a day in the morning, 18 days for the day); b) Methotrexate 15 mg IM once a week; c) hepatoprotector (heptor 400 mg 1 tablet 1 time per day-22 days); d) Folic acid 0.1 mg 2t 2 pd -6 days; e) Desensitizing therapy (200 ml of 0.9% Sodium Chloride-20 days); f) Local therapy (Komfoderm; Salicyl-dermatol ointment-22 days); g) Physiotherapeutic methods. With complex treatment, the trunk skin showed rashes regression, up to residual hyperpigmentation. The rash regression was 50% in the form of a decrease in the brightness of erythema in the palms, a decrease in peeling and the number of papular elements. Similar processes occurred on the skin of the feet, but with the preservation of large-plate peeling. A detailed literature analysis of known methods of treatment of psoriasis, with a comparison of new and traditional methods was performed. In recent years, the treatment of psoriasis has become more focused on targeted biological drugs. New methods of treatment not only demonstrate optimistic results, but also lead to a deeper understanding of the immunopathogenetic pathways of psoriasis, identifying new potential targets for therapeutic intervention and diagnosis. Our comprehensive approach has allowed us to establish one of the ways to achieve effective treatment.Key words: Psoriasis, Pharmacology, Symmetry, Paradoxical reaction, Physiotherapy, Papules, Rashes, peeling of the skin.